PENDEKATAN METODE BELAJAR TUNTAS DALAM MENINGKATKAN PRESTASI BELAJAR MENGARANG BAHASA INDONESIA - Siantiung, Welly (Makassar Journal of Social Sciences, 2015)
Abstract: The aim of this study was: (a) Determine the increase in Indonesian learning achievement after the implementation of Study Completed, (b) Determine the influence of motivation to learn Indonesian after the implementation of methods Study Completed. This study used action research (action research) a total of three rounds. Each round consists of four phases: design, activities and observation, reflection, and refisi. The targets of this research were students of class IX SMAN 8 Makassar. Data obtained in the form of a formative test results, observation sheet teaching and learning activities. student achievement has increased from cycle I to III. Results showed that 3 cycle analysts namely, the first cycle (63.99%), Cycle II (76.66%), the third cycle (86.66%). Results from this study is the teaching methods Learning Completed through shared reading activity can be a positive influence on the motivation of class X student of SMAN 8 Makassar and this model can be used as an alternative learning Indonesian